THE REPRESENTATION OF BALI NINE EXECUTION CASE - Istiqomah, Intan Aulia (2016)
This study investigates the representation of Bali Nine Execution Case in The Jakarta Post and The ABC by employing ideological square which is proposed by Van Dijk (2000). The analysis focuses on two semantic macro-strategies of positive self-presentation and negative other-presentation which are realized through the use of discursive strategies. Qualitative descriptive method is used to analyze how the Bali Nine Execution Case is represented in the two newspapers. Two articles from each newspaper become the sample of analysis to conduct the study. The findings show that The ABC and The Jakarta Post represent the same issue differently. The use of discursive strategies plays fundamental role in the representation of Bali Nine Execution Case. In representing the issue, The ABC uses a lot of discursive strategies, such as hyperbole, victimization and dramatization as the most frequent strategies to form the positive self-presentation and negative other-presentation. On the other hand, only several discursive strategies are found in The Jakarta Post's articles, such as disclaimer and vagueness as the most frequent strategies. Moreover, The Jakarta Post only creates the form of positive self-presentation, which is different from how The ABC represents the issue. Another finding reveals that there is ideology implied behind the representation of Bali Nine Execution Case in each newspaper. Partiality is found in The ABC, while neutrality is found in The Jakarta Post.; Penelitian ini bertujuan untuk menginvestigasi bagaimana representasi dari kasus eksekusi Bali Nine dalam koran The Jakarta Post dan The ABC dengan menggunakan teori ideological square dari Van Dijk (2000). Penelitian ini berfokus pada dua semantic makro strategi, yaitu positive self-presentation dan negative other-presentation yang terlihat melalui penggunaan discursive strategy. Metode deskriptif kualitatif digunakan untuk menganalisis bagaimana kasus eksekusi Bali Nine direpresentasikan di dalam kedua koran tersebut. Dua artikel dari masing-masing koran menjadi sampel penelitian ini. Dari hasil penelitian, terlihat bahwa The ABC dan The Jakarta Post merepresentasikan isu yang sama secara berbeda. Penggunaan discursive strategy menjadi hal yang penting dalam merepresentasikan kasus eksekusi Bali Nine. Dalam merepresentasikan isu ini, The ABC menggunakan banyak discursive strategy seperti hyperbole, victimization dan dramatization untuk membuat positive self-presentation dan negative other-presentation. Sementara itu, The Jakarta Post hanya menggunakan beberapa discursive strategy seperti disclaimer dan vagueness. The ABC hanya menggunakan bentuk positive self-presentation dalam merepresentasikan isu eksekusi, hal ini berbeda dari bagaimana The ABC merepresentasikan isu ini. Hasil lain dari penilitian ini ialah ditemukannya ideologi dari masing-masing koran yang didapat dari representasi kasus eksekusi Bali Nine.